USE OF CHROMIC DYES IN TEXTILE DESIGN AND A SAMPLE DESIGN WITH CHROMIC DYES - Mehmet Zahit BİLİR (International Journal of Eurasia Social Sciences, 2018)
In today’s global markets with quite hard competitive conditions, countries should serve different highly competitive products and designs to the markets. Textile industry has adapted itself to ever changing consumptive behaviors of the consumers and has expanded its product range including various high value-added innovative products and smart textiles. Chromic textiles are among these innovative designs. In this study, initially information was provided about chromic dyes placed in smart textiles and potential use of chromic dyes in textile industry and sample designs were presented for the use of chromic dyes over the textile surfaces with screen printing method. It was proved in this study that screen printing could conveniently be used in smart textile design and chromic and classical dyes could together be used in the same design. It was finally concluded that this and similar designs may improve the competitive power of the textile industry in global markets.